YES Problem: g(c(x,s(y))) -> g(c(s(x),y)) f(c(s(x),y)) -> f(c(x,s(y))) f(f(x)) -> f(d(f(x))) f(x) -> x Proof: DP Processor: DPs: g#(c(x,s(y))) -> g#(c(s(x),y)) f#(c(s(x),y)) -> f#(c(x,s(y))) f#(f(x)) -> f#(d(f(x))) TRS: g(c(x,s(y))) -> g(c(s(x),y)) f(c(s(x),y)) -> f(c(x,s(y))) f(f(x)) -> f(d(f(x))) f(x) -> x Matrix Interpretation Processor: dim=2 interpretation: [f#](x0) = [0 1]x0, [g#](x0) = [1 0]x0, [1 0] [d](x0) = [0 0]x0, [2 1] [0] [f](x0) = [0 2]x0 + [1], [0] [g](x0) = [1], [0 0] [0 1] [c](x0, x1) = [1 0]x0 + [0 0]x1, [2 1] [2] [s](x0) = [0 1]x0 + [1] orientation: g#(c(x,s(y))) = [0 1]y + [1] >= [0 1]y = g#(c(s(x),y)) f#(c(s(x),y)) = [2 1]x + [2] >= [1 0]x = f#(c(x,s(y))) f#(f(x)) = [0 2]x + [1] >= [0] = f#(d(f(x))) [0] [0] g(c(x,s(y))) = [1] >= [1] = g(c(s(x),y)) [2 1] [0 2] [2] [1 0] [0 2] [2] f(c(s(x),y)) = [4 2]x + [0 0]y + [5] >= [2 0]x + [0 0]y + [1] = f(c(x,s(y))) [4 4] [1] [4 2] [0] f(f(x)) = [0 4]x + [3] >= [0 0]x + [1] = f(d(f(x))) [2 1] [0] f(x) = [0 2]x + [1] >= x = x problem: DPs: TRS: g(c(x,s(y))) -> g(c(s(x),y)) f(c(s(x),y)) -> f(c(x,s(y))) f(f(x)) -> f(d(f(x))) f(x) -> x Qed